Pengaruh Motivasi Kerja, Budaya Organisasi dan Gaya Kepemimpinan Terhadap Kinerja Karyawan di PT. Natura Nuswantara Nirmala - Vina Nurpuji Setya Akbar; Nuryadi Nuryadi; Komarun Zaman (J-CEKI : Jurnal Cendekia Ilmiah, 2024)
This study aims to analyze the influence of work motivation, organizational culture, and leadership style on employee performance at PT Natura Nuswantara Nirmala. The results show that work motivation has a positive and significant effect on employee performance. Motivation in the form of rewards and development programs has been proven to significantly improve performance. Furthermore, a supportive organizational culture also positively influences employee performance, where good values and work environment encourage employees to work more effectively and efficiently. Transformational leadership style also has a positive and significant impact on employee performance, providing clear direction and motivating performance improvement. Overall, work motivation, organizational culture, and leadership style collectively have a positive and significant influence on employee performance at PT Natura Nuswantara Nirmala.